Was China's zero-COVID policy the right choice? The multiple factor analysis of variables that affected the course of COVID-19 pandemic in China - Sobczak, Marharyta; Pawliczak, Rafał (Frontiers in Public Health, 2023)
Background: After three years of COVID-19 pandemic and Zero-COVID policy, the rapid increase in number of daily COVID-19 infections was observed in China since November-December 2022. Therefore, we decided to analyze the factors, which have been related with COVID-19 pandemic in China.Methods: The multiple factor analysis was conducted, using the data from public available databases from the beginning of COVID-19 pandemic to January 30, 2023.Results: Our study showed that each year of pandemic in China had different profiles and can be described by different variables: 2020 was characterized by restrictions, such as international travel controls, stay at home requirements, and also by health system policies including contact tracing and protection of elderly people; 2021 by Alpha, Beta, Gamma and Delta variants; 2022 by new cases per million, Omicron lineages, and a few restrictions-related variables; and 2023 was mainly described by number of new deaths per million and Omicron variant 22B (BA.5), but also by testing and vaccination policies, as well as count of people fully vaccinated per hundred and total boosters per hundred.The COVID-19 pandemic has changed over time. Therefore, the anti-pandemic policies implemented must be dynamic and adapted to the current situation. This is a provisional file, not the final typeset article Unfortunately, SARS-CoV-2 virus is mutating all of the time, leading to origination of the new virus lineages with different genetic variation. Hence, different lineages of virus have different characteristics: some of them may be relatively harmless, and others are more dangerous, as they can spread easier or be resistant for treatment. Therefore, SARS-CoV-2 lineages are marked as variants under monitoring, variants of interest and variants of concern (4). At March 15, 2023 World Health Organization (WHO) has updated the definitions of virus variants as well as the primary actions for particular classification (5). On the day of Mach 30, 2023 there was one SARS-CoV-2 lineage defined as variant of interest -XBB.1.5, and there were seven lineages defined as variants under monitoring: